Updating of an instrumented building model considering amplitude dependence of dynamic resonant properties extracted from seismic response records. Issue 4 (14th September 2015) - Omenzetter, Piotr; Butt, Faheem
Summary: This paper presents system identification and numerical analyses of a three‐story RC building. System identification was performed using 50 earthquake response records to obtain the frequencies and damping ratios, taking into account soil–structure interaction. Trends in the resonant parameters were correlated with the peak response accelerations at the roof level. A general trend of decreasing resonant frequencies with increasing level of response was observed and quantified, whereas for the damping ratios, no clear trends were discernible. A series of finite element models (FEMs) of the building were updated using a sensitivity‐based method with a Bayesian parameter estimation technique to follow the changes in the resonant frequencies with response amplitude. The FEMs were calibrated by tuning the stiffness of structural and non‐structural components and soil. The updated FEMs were used in time history analyses to predict and assess the building seismic performance at the serviceability limit state. It was concluded that the resonant frequencies depend strongly on the response magnitude, even for low‐to‐moderate levels of shaking. The structural and non‐structural components and soil make contributions to the overall building stiffness that depends on the level of shaking. The FEM calibrated to the largest responses was the least conservative in predicting the serviceability limit state inter‐story drifts, but the building performed satisfactorily. Copyright © 2015 John Wiley & Sons, Ltd.